2021
DOI: 10.1037/rel0000302
|View full text |Cite
|
Sign up to set email alerts
|

Initial psychometric properties of the Spiritual Bypass Scale in an Indian college student sample.

Abstract: The purpose of the present study was to examine the psychometric characteristics of the Spiritual Bypass Scale-13 (SBS-13) in India. English-speaking Indian graduate students (N ϭ 250) at a large university participated. Students were 22 years of age on average, and most were women, Indian, Hindu, and never married. The main measure of interest was the SBS-13. Convergent validity measures included the Religious Commitment Inventory-10, Sources of Spirituality Scale, and the Brief RCOPE. The factor structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…Results supported the two-factor and higher order factor structure of the SBS-13 in MLUS, extending the research by Fox et al (2017Fox et al ( , 2020Fox & Picciotto, 2019;Picciotto et al, 2018;Taylor et al, 2021;Toussaint et al, 2021) to a religious group for whom spiritual bypass may be especially relevant.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Results supported the two-factor and higher order factor structure of the SBS-13 in MLUS, extending the research by Fox et al (2017Fox et al ( , 2020Fox & Picciotto, 2019;Picciotto et al, 2018;Taylor et al, 2021;Toussaint et al, 2021) to a religious group for whom spiritual bypass may be especially relevant.…”
Section: Discussionsupporting
confidence: 82%
“…Results revealed that all standardized factor loadings were significant ( p < .001) for items within their respective subscales, although fit for the original model was not adequate χ 2 (64) = 304.83, p < .001, RMSEA = .105, CFI = .911, SRMR = .062. Modification indices suggested that correlating error terms for Items 1 and 2 (similarly to Taylor et al, 2021), Items 3 and 4 (e.g., Fox et al, 2017; Picciotto et al, 2018; Taylor et al, 2021; and Toussaint et al, 2021), and Items 8 and 9 (e.g., Picciotto et al, 2018) would improve model fit, and these covariations were specified. Further, as in past studies, the factor loading for the reverse-coded Item 1 was negative, so Item 1 in its nonrecoded form was subsequently used (e.g., Taylor et al, 2021; Toussaint et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, Cronbach's α was .91 for psychological avoidance, was .89 for spiritualizing, and was .92 for all 13 items. The SBS-13 has not been validated in Muslims, and exploratory factor analysis of the measure here (N = 350) yielded similar results to validation studies in Brazil (Picciotto et al, 2017) and India (Toussaint et al, 2021). That is, standardized factor loadings for the nine psychological avoidance items ranged from .61 to .84, and for the four spiritualizing items from .42 to .87.…”
Section: Methodssupporting
confidence: 61%